Application of pollen germination media on stigmas during pollination increases seed set in east African highland cooking bananas (Musa spp.) - Waniale, A.; Swennen, Rony L.; Mukasa, S.; Tugume, Arthur K.; Kubiriba, Jerome; Tushemereirwe, Wilberforce K.; Amah, D.; Tumuhimbise, Robooni (MDPI, 2021)
Seed set in East African Highland Cooking bananas (EAHBs) is extremely low and therefore hampers breeding. Pollen–pistil interaction is a key contributing factor. We assessed the effect of pollen germination media (PGM) on seed set in EAHBs. Five EAHB cultivars were pollinated with pollen from the wild banana ‘Calcutta 4’. Glucose-based PGM sprayed on freshly emerged stigmas significantly increased seed set per 100 fruits per bunch. Increases were 73.5% in ‘Enzirabahima’, 39.9% in ‘Mshale’, and 302.4% in ‘Nshonowa’. However, PGM did not increase seed set in the female sterile ‘Mlelembo’ and ‘Nakitembe’. As larger bunches were more fertile, good field management practices are also recommended to get more seed to improve breeding efficiency.